2023
DOI: 10.1371/journal.pgph.0001268
|View full text |Cite
|
Sign up to set email alerts
|

“Right now we are scared of each other, we fear everyone, the whole world has COVID”: The impact of COVID-19 on young female sex workers in Kampala, Uganda, during national lockdowns in 2020–2021

Abstract: In 2020–2021 the COVID-19 pandemic led to multiple and diverse global public health response strategies globally and in Uganda to slow the spread of the virus by promoting wearing face coverings in public, frequent hand washing, physical distancing, restricting travel, and imposing home lockdowns. We conducted 146 interviews over four rounds of phone-follow up calls over 15 months with 125 young female sex workers coinciding in time with four different government-imposed lockdown periods in Kampala, Uganda, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This combination of factors has signi cant consequences for a population with a large burden of HIV and higher rates among women (37). Similarly, the current study underscores the vulnerability of women in these transactional relationships, shedding light on unequal power dynamics and compromised ability to negotiate safer sex practices (22,34,38). This nding is consistent with literature on gender-based violence that indicates that exploitation within intimate relationships further undermines women's ability to remain healthy in adverse conditions (39)(40)(41).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…This combination of factors has signi cant consequences for a population with a large burden of HIV and higher rates among women (37). Similarly, the current study underscores the vulnerability of women in these transactional relationships, shedding light on unequal power dynamics and compromised ability to negotiate safer sex practices (22,34,38). This nding is consistent with literature on gender-based violence that indicates that exploitation within intimate relationships further undermines women's ability to remain healthy in adverse conditions (39)(40)(41).…”
Section: Discussionmentioning
confidence: 66%
“…In our context, we found that many women experienced abandonment by men (partners), which increased the burden of work and compounded the toll of economic hardships on women's mental and physical well-being. Some women, grappling with severe nancial di culties and food insecurity, turned to short-term sexual survival strategies (22,33). Long before the pandemic, several studies have highlighted the complex and intersectional relationship between socioeconomic status and sexual health outcomes, including HIV and unwanted pregnancies, within informal settlements in Uganda and other sub-Saharan African countries (22,(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations